Penerapan Metode Demonstrasi dalam Upaya Meningkatkan Kemampuan Belajar Matematika Materi Pecahan Siswa Kelas II di SDN 1 Trayu - Fahrur Rozi Hadiyanto; Diana Ayu Puspita Hapsari (Griya Journal of Mathematics Education and Application, 2023)
Education is the process of promoting and developing independence, and the capacity to support oneself without the help of others. Because the search for truth must be supported by theorems, properties, and postulates once established. Another science that can be learned through reason is mathematics, which carefully, precisely, and accurately defines its terms. Based on the trial tests given to class II students at SDN 1 Trayu, Singorojo District, Kendal Regency regarding fractional material, it proves that students still have limited knowledge about the material in these subjects. The research was conducted to increase students' understanding and interest in learning fractional material through demonstrative techniques using cardboard models and colored pencils. The research was conducted in two cycles, starting with planning, implementing actions, observing, reflecting, and ending with the preparation of the next cycle. There were 21 grade II students at SD N 1 Trayu who were the research subjects. The results of the research are evident from the increase in student learning outcomes which were originally in the pre-cycle the percentage of completeness was only 33.33%, then in cycle 1 the percentage of completeness was 52.38% and in cycle II it increased significantly to 90.47% the percentage of completeness.